Energy consumption and CO2 emissions: a threshold error correction and threshold Granger Causality Analysis - ÇAĞLAYAN AKAY, EBRU (MULTI-SCIENCE PUBL CO LTD, 2013)
Energy is one of the key factors of maintaining a quality life with economic and social development. Accordingly, measuring the development level of a given country can be possible by considering the development level of the energy sector of that country. The purpose of this study is to examine the relation between the consumption of several energy resources classified as fossil, renewable and nuclear resources with carbon dioxide emission. For this purpose, monthly data of the U.S.A. covering the period of 1990-2011 were used and Threshold Error Correction and Threshold Granger Causality analyses were carried out with the Hansen and Seo (2002) approach. Findings of the study indicate the presence of a causality relation between the consumption levels of the discussed energy resources and CO2 emission.
Keywords: CO2 Emissions; Energy Consumption; Threshold Error Correction Model; ECONOMIC-GROWTH; ELECTRICITY CONSUMPTION; DEVELOPING-COUNTRIES; CARBON EMISSIONS; TIME-SERIES; UNIT-ROOT; COINTEGRATION; INCOME; CHINA; TESTS